Links between microbial biomass and necromass components in the top- and subsoils of temperate grasslands along an aridity gradient - Zhang, Xinying; Dai, Guohua; Ma, Tian; Liu, Nana; Hu, Huifeng; Ma, Wenhong; Zhang, Jin-Bo; Wang, Zhiheng; Peterse, Francien; Feng, Xiaojuan (Geoderma, 2020)
Microbial carbon has recently been highlighted to play a key role in the formation and persistence of soil organic carbon, bearing significant implications for regulating ecosystem carbon stocks under global changes. However, microbial carbon distribution and the link between biomass and necromass components are poorly understood in natural soils, especially at depth. Here, we employ various microbial biomarkers, including phospholipid fatty acids (PLFAs), amino sugars and glycerol dialkyl glycerol tetraethers (GDGTs), to investigate the spatial distribution patterns of microbial biomass and necromass components in the top- (0–10 cm) versus subsoils (30–50 cm) across Chinese temperate grasslands along an aridity gradient. We find that bacterial necromass components are better preserved relative to bacterial biomass in the sub- than topsoil, possibly due to a stronger association of microbial necromass with calcium and/or lower nitrogen competition between plants and microbes at depth in these neutral-to-alkaline soils. As a result, there is a stronger link between bacterial necromass components (especially for core lipid branched GDGTs and muramic acid) and their producers (reflected by intact polar lipid-derived branched GDGTs) in the sub- than topsoil, while such a trend is not observed for fungi- or archaea-derived components. Furthermore, using linear mixed effect model analyses, we find that aridity index best explains the concentration variance of most microbial biomarkers in the topsoil, whereas edaphic properties (i.e., pH and macronutrients) also contribute significantly to their variance in the subsoil. These findings highlight different links between microbial necromass and biomass components and distinct preservation mechanisms for microbial carbon at different soil depths, which is crucial for improved understanding of microbial carbon sequestration potentials at different depths in a changing environment.
Keywords: Amino sugars; GDGTs; Microbial carbon; Necromass; PLFAs